Approaching EdD Program Redesign as a Problem of Practice - Lesley F Leach; Juanita M Reyes; Credence Baker; Ryan Glaman; Jordan M Barkley; Don M Beach; J Russell Higham; Kimberly Rynearson; Mark Weber; Tod Allen Farmer; Randall Bowden; Jesse Brock; et al. (Impacting Education, 2020)
As members of the Carnegie Project on the Education Doctorate (CPED), universities across the United States are restructuring EdD programs to better prepare professional practitioners with the practical skills and theoretical knowledge needed to improve the educational environments that they serve. The hallmark of these programs is often the dissertation in practice, a scholarly investigation within which students define a problem of practice and then systematically test solutions to that problem. In this study, we investigate the experiences of university faculty participating in the redesign of an Educational Leadership EdD program who approach the redesign as a problem of practice. Root causes of identified program issues are presented in addition to the changes implemented in the redesigned program to improve upon the problem of practice.